A boundary element procedure to analyze the thermomechanical contact problem in 3D microelectronic packaging. (June 2020) - Vallepuga-Espinosa, J.; Ubero-Martínez, I.; Rodríguez-Tembleque, L.; Cifuentes-Rodríguez, J.
Highlights: Double iterative boundary element formulation for the thermoelastic contact of 3D microelectronic packaging. The influence of the clamping pressure and the geometry of the heatsink is analyzed. Results reveals that thermal variables are clearly affected by the clamping pressure of the microelectronic packaging. The height of heatsink can result in changes in the size of the contact zone. Abstract: The interface between two surfaces in contact is formed by numerous microcontacts and gaps separating both surfaces. The heat flow from one surface to the other has to overcome these gaps by means of a thermal contact resistance. In microelectronic packaging it is necessary to evacuate the heat from the microprocessor, so it is important to have a great conductance of the heat flow between the microprocessor and the heatsink. This work studies the 3D microchip-heatsink contact in microelectronic packaging using the boundary element method. The formulation includes a variable thermal contact resistance along the contact zone formed in the interfase between the microchip and the heatsink. The thermal contact resistance is a function of the contact normal traction, so the thermal and the thermoelastic problems are coupled. The values of the final thermal and mechanical variables of the boundary of the microelectronic packaging and the thermal contact resistance are obtained by a double iterative schema.